2017
DOI: 10.3390/f8110406
|View full text |Cite
|
Sign up to set email alerts
|

Wild Apple Growth and Climate Change in Southeast Kazakhstan

Abstract: Wild populations of Malus sieversii [Ldb.] M. Roem are valued genetic and watershed resources in Inner Eurasia. These populations are located in a region that has experienced rapid and on-going climatic change over the past several decades. We assess relationships between climate variables and wild apple radial growth with dendroclimatological techniques to understand the potential of a changing climate to influence apple radial growth. Ring-width chronologies spanning 48 to 129 years were developed from 12 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In addition, wild populations of the fruit forests are in direct proximity to cultivated apple orchards which represent a serious problem (Zhang et al, 2014). The buffer protection zone along the natural populations is often not maintained (Panyushkina et al, 2017). Apart from alien plant species, there are threats to the wild fruit forests from insect pests and diseases of wild apple trees and of other wild fruit species (Jashenko and Tanabekova, 2019).…”
Section: Blue Colour Is Correction For Manuscriptmentioning
confidence: 99%
“…In addition, wild populations of the fruit forests are in direct proximity to cultivated apple orchards which represent a serious problem (Zhang et al, 2014). The buffer protection zone along the natural populations is often not maintained (Panyushkina et al, 2017). Apart from alien plant species, there are threats to the wild fruit forests from insect pests and diseases of wild apple trees and of other wild fruit species (Jashenko and Tanabekova, 2019).…”
Section: Blue Colour Is Correction For Manuscriptmentioning
confidence: 99%
“…Changes in tree growth response to climate occurred in the next lower vegetation zone ca. 1970, with increasing sensitivity to spring precipitation [65]. I. hauseri outbreaks are known to be associated with drought [11,12].…”
Section: Warming Climatementioning
confidence: 99%
“…Spring 2016 precipitation in Almaty Oblast was in the highest 10th percentile since 1940 [64]. Spring moisture shortens the montane growing season in the Ile Alatau due to snow insulation and/or cold rains cooling the soil [65,69]. Drought-responsive multi-voltine bark beetles, particularly Ips, often respond rapidly to drought, and terminate abruptly with a shift to wetter conditions [2].…”
Section: Warming Climatementioning
confidence: 99%
“…Following the increasing mortality of M. sieversii , the wild fruit forest ecosystem has been seriously damaged and some wild fruit forest region degraded obviously ( Fang et al, 2019 ). One study showed that M. sieversii growth was associated with spring precipitation and winter temperature ( Panyushkina et al, 2017 ). However, whether extreme climate change has positive or negative effects on this forest growth has not been determined, and we wonder if the degradation of wild fruit forest may be caused by extreme change, these scientific problems are addressed in this study.…”
Section: Introductionmentioning
confidence: 99%